CLINICAL ASPECTS OF BILE CULTURE IN PATIENTS UNDERGOING LAPAROSCOPIC CHOLECYSTECTOMY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: The estimated prevalence of gallstone disease in India ranges from 2% to 9%. Cholecystectomy is one of the most common surgical procedures in India. In 10–70% of individuals undergoing laparoscopic cholecystectomy, bile culture detects bacteria; in older patients, those with acute cholecystitis, or those who have had preoperative ERCP, the percentage reaches up to 59.7%. The most prevalent pathogen is Escherichia coli. Since many isolates are resistant to common preventative medicines, cultures aid in guiding antibiotic therapy. Methods: This cross-sectional study was conducted in the patients admitted for cholecystectomy in the department of General Surgery in a tertiary care hospital in Chennai.60 patients were included in the study. All patients undergoing laparoscopic/open cholecystectomy above 18 years of age were included for the study. Patients with previous biliary tract surgery, patients in immunocompromised status and pregnant women were excluded from the study. Results: Among 60 patients, 31 to 40 years were 25 % and 51 to 60 years were 25%. Mean age of the participants was 46.85±14.52 years. 23.3% were males and 76.7% were females. Among the symptoms all patients had abdominal pain followed by nausea/vomiting, fever, and dyspepsia. There was no growth in 53% of bile culture, remaining 47% were various micro-organisms like Escherichia coli, Klebsiella, Proteus vulgaris, Enterococcus, Salmonella, and Shigella. Conclusion: Ceftriaxone and PIPTAZ demonstrated the greatest degree of effectiveness against the pathogens like E. coli and other bacteria. Antibacterial activity against suspected causal organisms, the severity of the cholecystitis, and the local susceptibility pattern are all factors that need to be taken into consideration while prescribing antibiotics.